Towards New Sharia Governance for Islamic Financial Institutions - Abdulazeem Abozaid (Justicia Islamica, 2021)
Since its inception a few decades ago, the Islamic banking and finance industry has been regulating itself in terms of Sharia governance. Although some regulatory authorities from within the industry, such as the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) and Islamic Financial Services Board (IFSB), the Islamic banking and finance industry remains largely self-regulated. This is because none of the resolutions or the regulatory authorities' standards are binding on the Islamic financial institution except when it willingly chooses to bind itself by them. Few countries have enforced some Sharia-governance-related regulations on their Islamic banks. However, in most cases, these regulations do not go beyond the requirement to formulate some Sharia-controlling bodies, which are practically left to the same operating banks. Furthermore, some existing regulatory authorities' standards and resolutions are conflicted with other resolutions issued by Fiqh academies. The paper addresses those issues by highlighting the shortcomings and proposing the necessary reforms to help reach effective Shariah governance that would protect the industry from within and help it achieve its goals. The paper concludes by proposing a Shariah governance model that should overcome the challenges addressed in the study.